Depression and perceived stress among perinatal women living with HIV in Nigeria - Akinsolu, Folahanmi T.; Abodunrin, Olunike R.; Lawale, Abisola A.; Bankole, Samuel A.; Adegbite, Zaniab O.; Adewole, Ifeoluwa E.; Olagunju, Mobolaji T.; Ola, Oluwabukola M.; Dabar, Anita M.; Sanni-Adeniyi, Rukayat A.; Gambari, Aisha O.; Njuguna, Diana Wangeshi; et al. (Frontiers in Public Health, 2023)
Background: Pregnancy and postpartum periods are crucial stages for women's mental health, and women living with HIV are particularly susceptible to depression and psychological stress due to various factors. This study investigated the prevalence and associated factors of depression and perceived stress among women living with HIV during their perinatal period in Ibadan, Nigeria.A cross-sectional survey was conducted in three HIV treatment centers in Ibadan, Nigeria, among women living with HIV between the ages of 19 and 49 who were either pregnant or had given birth within the last two years. The study was conducted from September 2022 to December 2022. An interviewer-administered questionnaire was used to collect the data from the participants. Ethical approval and informed consent were obtained, and data were analyzed using the Statistical Package for Social Science version 26.The study included 402 participants, of whom 69.0% and 78.0% reported symptoms of depression and perceived stress, respectively. However, 15.2% of the participants have comorbid depression and stress. Positive partner status was significantly associated with lower perceived depression, while gestational age between 29-40 weeks was significantly associated with lower perceived stress. The co-occurrence of depression and perceived stress was associated with partner status, income level, family support, gestational age, and years on antiretroviral therapy.The high prevalence of depression, perceived stress, and their co-occurrence among women living with HIV during the perinatal period call for incorporating mental health care into routine maternal healthcare for all women, particularly those living with HIV. This finding emphasizes the need for public health efforts to prioritize perinatal mental health and improve access to care and support for women and their partners.